Assessing Blood Flow in an Intracranial Stent: A Feasibility Study of MR Angiography Using a Silent Scan after Stent-Assisted Coil Embolization for Anterior Circulation Aneurysms - Irie, R.; Suzuki, M.; Yamamoto, M.; Takano, N.; Suga, Y.; Hori, M.; Kamagata, K.; Takayama, M.; Yoshida, M.; Sato, S.; Hamasaki, N.; Oishi, H.; et al. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Blood flow in an intracranial stent cannot be visualized with 3D time-of-flight MR angiography owing to magnetic susceptibility and radiofrequency shielding. As a novel follow-up tool after stent-assisted coil embolization, we applied MRA by using a Silent Scan algorithm that contains an ultrashort TE combined with an arterial spin-labeling technique (Silent MRA). The purpose of this study was to determine whether Silent MRA could visualize flow in an intracranial stent placed in the anterior circulation. MATERIALS AND METHODS: Nine patients treated with stent-assisted coil embolization for anterior circulation aneurysms underwent MRAs (Silent MRA and TOF MRA) and x-ray digital subtraction angiography. MRAs were performed in the same session on a 3T unit. Two neuroradiologists independently reviewed the MRA images and subjectively scored flow in a stent as 1 (not visible) to 4 (excellent) by referring to the latest x-ray digital subtraction angiography image as a criterion standard. RESULTS: Both observers gave MRA higher scores than TOF MRA for flow in a stent in all cases. The mean score for Silent MRA was 3.44 ± 0.53, and for TOF MRA, it was 1.44 ± 0.46 (P < .001). CONCLUSIONS: Silent MRA was able to visualize flow in an intracranial stent more effectively than TOF MRA. Silent MRA might be useful for follow-up imaging after stent-assisted coil embolization, though these study results may be only preliminary due to some limitations.